Women with polycystic ovary syndrome have elevated serum concentrations of and altered GABAA receptor sensitivity to allopregnanolone - Hedström, Helena; Bäckström, Torbjörn; Bixo, Marie; Nyberg, Sigrid; Wang, Mingde; Gideonsson, Ida; Turkmen, Sahruh (Clinical endocrinology (Oxford), 2015)
Summary Objective Several studies have reported that γ‐aminobutyric acid (GABA) ergic circuits are involved in the pathophysiology of polycystic ovary syndrome (PCOS). The progesterone metabolite allopregnanolone is a potent GABAA‐receptor‐modulating steroid, and patients may have increased concentrations of allopregnanolone or altered GABAA receptor sensitivity. We investigated both of these possibilities in this study. Patients We enrolled 9 women with PCOS and 24 age‐matched eumenorrhoeic controls, who were divided into two groups by body mass index (BMI) (16 normal weight and 8 overweight). Measurements We investigated the effects of allopregnanolone injection on GABAA receptor sensitivity in both groups of women. All women received a single intravenous dose of allopregnanolone (0·050 mg/kg). GABAA receptor sensitivity was assessed with the saccadic eye velocity (SEV) over 30° (SEV30°), the SEV30°/allopregnanolone concentration ([Allo]) ratio, and sedation, which were measured together with serum allopregnanolone at intervals for 180 min after injection. The controls were tested in the follicular phase of the menstrual cycle. Results Baseline allopregnanolone concentrations were higher in the PCOS women than in the normal‐weight (P = 0·034) and overweight controls (P = 0·004). The allopregnanolone concentrations after injection were higher in the PCOS women (P = 0·006) and overweight controls (P = 0·037) than in the normal‐weight controls. All groups showed a decline in the SEV30°/[Allo] ratio after injection. Allopregnanolone had a smaller effect on the SEV30°/[Allo] ratio in the overweight women (PCOS, P = 0·032; controls, P = 0·007) than in the normal‐weight controls. The sedation score after allopregnanolone injection was lower in the PCOS patients than in the controls, but was not different between the two control groups. Conclusions PCOS women had elevated baseline allopregnanolone concentrations compared with follicular‐phase controls. All overweight women (PCOS and controls) were less sensitive to allopregnanolone than normal‐weight controls.